Cine de crítica social contra el franquismo con intervención (austro)húngara: Surcosy ¡Bienvendio, Mister Marshall! - Lénárt, András (Acta Hispanica, 2013)
From the second half of the 1950s the Spanish society experienced some new phenomena. The inflexibility of the Franco regime started to slacken, the unsatisfied masses were not afraid to express their opinion occasionally. Besides university students, the members of the film industry finally dared to give voice to their disapproval in public. In accordance with the basic points of their doubts, anxieties and dissapointments (disseminated through newspaper articles and lectures), the most important filmmakers set out to shoot movies in order to criticize the Francoist society and the contradictions of the political system. Two gems of this cinematographic mission were Furrows (Surcos, José Antonio Nieves Conde, 1951) from a Hungarian film producer and Welcome Mr. Marshall! (¡Bienvenido, Mister Marshall!, Luis García Berlanga, 1953). In this paper I highlight those components of the two films that can be regarded as strong critiques of the Spanish dictatorship.